Predictors of low estimated glomerular filtration rate after living kidney donation in a Southeast Asian population from Singapore. Issue 10 (October 2017) - Tan, Ru Yu; Allen, John C; Kee, Terence; Jafar, Tazeen H
Abstract: Aim: Post‐donation kidney function has not been well characterized in the Southeast Asian population. We studied a retrospective cohort of 174 living kidney donors at Singapore General Hospital between 1976 and 2012, evaluated patterns of change in kidney function using quantile regression analysis and investigated for predictors of low estimated glomerular filtration rate (eGFR) < 60 mL/min per 1.73m 2 . Median follow‐up time (range) was 7.8 (0.1–33.8) years following donor nephrectomy. Results: Of the donors, 43.1% regained 75% or more of pre‐nephrectomy eGFR after 5 years post‐donation; 9.8% exhibited 100% recovery to pre‐nephrectomy eGFR. High pre‐nephrectomy eGFR was protective for risk of low post‐donation eGFR, with a 6% risk reduction for each unit increase in pre‐nephrectomy eGFR (odds ratio, 0.94; 95% confidence interval, 0.91–0.97; P = 0.002). This relationship was stronger in the short term (>6 months to < 5 years) than medium to long term (5 years or longer) (interaction P = 0.052). Conclusion: In general, kidney function is well preserved following kidney donation in Southeast Asian donors. Pre‐nephrectomy eGFR is a good predictor of post‐donation eGFR, especially in the short‐term. Summary at a Glance: This is a long‐term follow‐up study of South‐East Asian donors from a single‐centre in Singapore, evaluating the association between pre‐donation factors and post‐donation kidney function.